Kesahihan dan Ke-Da‘îf-an Hadîth “Perkara Halal yang Paling Dibenci Allah Adalah Talak” dan Implikasinya terhadap Konsep Talak - Amrulloh, Amrulloh (Marâji`: Jurnal Ilmu Keislaman, 2015)
The study deals with the discussion about the validity of hadîth about “the most despised matter by God is divorce” and its invalidity as well as the implication of each status of sahîh and da‘îf which rests in the hadîth towards the concept of lawfulness and detestation of divorce. For certain group of people this hadîth might seem wise, since it would be able to significantly decrease the number of divorce or to be a sort of “an ultimate weapon” for judge or parents to give advice for spouse who experience domestic rift. However, for other people the hadîth seems inconsistent. They argue that it is impossible for God to hate a lawful matter. Therefore, the hadîth is unique, since it is validated by a number of prominent Muslim scholars on one hand. On the other, there are also a number of noticeable Muslim scholars who believe the hadîth as da‘îf. Each group, however, build their argument on a common ground, i.e. conventional science of the critique of hadîth.